2015
DOI: 10.1038/nature14053
|View full text |Cite
|
Sign up to set email alerts
|

Broad CTL response is required to clear latent HIV-1 due to dominance of escape mutations

Abstract: Despite antiretroviral therapy (ART), HIV-1 persists in a stable latent reservoir1, 2, primarily in resting memory CD4+ T cells3, 4. This reservoir presents a major barrier to the cure of HIV-1 infection. To purge the reservoir, pharmacological reactivation of latent HIV-1 has been proposed5 and tested both in vitro and in vivo6–8. A key remaining question is whether virus-specific immune mechanisms including cytolytic T lymphocytes (CTL) can clear infected cells in ART-treated patients after latency is revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
439
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(456 citation statements)
references
References 34 publications
16
439
1
Order By: Relevance
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance. 24,25 Over the last decade, major advances have been made in engineering human T cells via introduction of chimeric antigen receptors (CARs) to enable specific lysis of pathogenic targets.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance. 24,25 Over the last decade, major advances have been made in engineering human T cells via introduction of chimeric antigen receptors (CARs) to enable specific lysis of pathogenic targets.…”
Section: Introductionmentioning
confidence: 99%
“…12 Early treatment also prevents the latent viral reservoir from becoming dominated by HIV-1 variants that have mutated to escape cytotoxic T lymphocytes (CTL); this has implications for both therapeutic vaccine design and HIV cure strategies. 13 Furthermore, earlier initiation of cART and higher nadir CD4 T-cell counts have been associated with the preservation of functional recall T-cell responses.…”
Section: Early Initiation Of Cart Facilitates Efficacious Immunotheramentioning
confidence: 99%
“…However, immunization in conjunction with cART may lead to a reversal of anergy by selective induction and activation of specific memory T-cell responses against a number of viral proteins. 3,20 By presenting viral proteins in novel ways, with or without specific adjuvants, or by presenting both immunodominant and subdominant epitopes, specific beneficial memory responses may be induced or augmented, 13 and T-cell anergy reversed. That said, even administered in the context of cART, therapeutic immunization is likely to have little efficacy if used without other concomitant immunotherapies due to the immunocompromised status of chronically HIV-1-infected patients.…”
Section: Essential Role Of Therapeutic Vaccines To Provide Antigenicmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that variable sequences can serve as immunodominant “decoys” that can absorb immune reactivity, driving the emergence of escape mutations and potentially precluding responses against conserved protective epitopes. 2935 The mechanisms of this preclusion, also referred to as immunodomination, 36 are varied. 37 , 38 Virus-specific T cells are responsible for controlling viremia in humans and macaques.…”
Section: Introductionmentioning
confidence: 99%